Bortezomib plus melphalan and prednisone in elderly untreated patients with multiple myeloma: updated time-to-events results and prognostic factors for time to progression - María-Victoria Mateos; José M. Hernández; Miguel T. Hernández; Norma C. Gutiérrez; Luis Palomera; Marta Fuertes; Pedro Garcia-Sanchez; Juán J. Lahuerta; Javier de la Rubia; María-José Terol; Ana Sureda; Joan Bargay; et al. (Haematologica, 2008)
Background New treatment options offering enhanced activity in elderly, newly diagnosed patients with multiple myeloma are required. One strategy is to combine melphalan and prednisone with novel agents. We previously reported an 89% response rate, including 32% complete responses and 11% near complete responses, in our phase 1/2 study of bortezomib plus melphalan and prednisone (VMP) in 60 newly diagnosed multiple myeloma patients with a median age of 75 years. Here, we report updated time-to-events data and the impact of poor prognosis factors on outcome.Design and Methods Updated analyses of time to biochemical progression and overall survival with VMP were conducted, and compared with those of historical controls treated with melphalan and prednisone. A univariate analysis was performed to evaluate the influence of known prognostic factors on the time to progression.Results After a median follow-up of 26 months, the median time to progression with VMP was 27.2 months, compared with 20.0 months with melphalan plus prednisone. The median overall survival with VMP was not reached versus 26 months with melphalan and prednisone; the survival rate at 38 months was 85% versus 38%, respectively. Time to progression was not significantly affected by elevated β2-microglobulin or lactate dehydrogenase levels, advanced age, or cytogenetic abnormalities, but was shorter in patients with albumin